VEGF‐D promotes pulmonary oedema in hyperoxic acute lung injury. Issue 2 (30th March 2016) - Sato, Teruhiko; Paquet‐Fifield, Sophie; Harris, Nicole C; Roufail, Sally; Turner, Debra J; Yuan, Yinan; Zhang, You‐Fang; Fox, Stephen B; Hibbs, Margaret L; Wilkinson‐Berka, Jennifer L; Williams, Richard A; Stacker, Steven A; et al.
Abstract: Leakage of fluid from blood vessels, leading to oedema, is a key feature of many diseases including hyperoxic acute lung injury (HALI), which can occur when patients are ventilated with high concentrations of oxygen (hyperoxia). The molecular mechanisms driving vascular leak and oedema in HALI are poorly understood. VEGF‐D is a protein that promotes blood vessel leak and oedema when overexpressed in tissues, but the role of endogenous VEGF‐D in pathological oedema was unknown. To address these issues, we exposed Vegfd ‐deficient mice to hyperoxia. The resulting pulmonary oedema in Vegfd ‐deficient mice was substantially reduced compared to wild‐type, as was the protein content of bronchoalveolar lavage fluid, consistent with reduced vascular leak. Vegf‐d and its receptor Vegfr‐3 were more highly expressed in lungs of hyperoxic, versus normoxic, wild‐type mice, indicating that components of the Vegf‐d signalling pathway are up‐regulated in hyperoxia. Importantly, VEGF‐D and its receptors were co‐localized on blood vessels in clinical samples of human lungs exposed to hyperoxia; hence, VEGF‐D may act directly on blood vessels to promote fluid leak. Our studies show that Vegf‐d promotes oedema in response to hyperoxia in mice and support the hypothesis that VEGF‐D signalling promotes vascular leak in human HALI. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.